Juvenile Granulosa Cell Tumor Mimicking HAIR-AN in a 4-year-old: A Case Report - Rachel Choe Kim; Ilya Goldberg; Trevor Van Brunt; Hamama Tul-Bushra; Rebecca Batiste; Andrew H. Lane; Helen Hsieh (Galenos Yayincilik, 2024)
Predominantly androgen secreting juvenile granulosa cell tumors (JGCT) are uncommon and few reports have been published. We present a case of a JGCT that presented with signs of prepubertal hyperandrogenism and insulin resistance to highlight the possible interaction between hyperandrogenemia and hyperinsulinism. A 4-year-old girl presented with acanthosis nigricans and hyperinsulinism, mimicking the hyperandrogenism, insulin resistance and acanthosis nigricans syndrome at an age much younger than is typical for this diagnosis. Laboratory studies revealed elevated insulin, inhibin A and B, and total testosterone. All laboratory results normalized after unilateral salpingo-oophorectomy. The final diagnosis was Stage 1A JGCT. This case highlights the importance of including ovarian tumors in the differential diagnosis when considering causes of virilization and insulin resistance. This case also suggests a potential relationship between excess testosterone secretion and hyperinsulinemia and strengthens evidence that hyperandrogenemia may promote hyperinsulinism in ovarian disease.